NRAGE, a p75 Neurotrophin Receptor-interacting Protein, Induces Caspase Activation and Cell Death through a JNK-dependent Mitochondrial Pathway - Amir H. Salehi; Steven Xanthoudakis; Philip Barker (2002)
The p75 neurotrophin receptor (p75NTR) mediates signaling events leading to activation of the JNK pathway and cell death in a variety of cell types. We recently identified NRAGE, a protein that directly interacts with the p75NTR cytosolic region and facilitates p75NTR-mediated cell death. For the present study, we developed an inducible recombinant NRAGE adenovirus to dissect the mechanism of NRAGE-mediated apoptosis. Induced NRAGE expression resulted in robust activation of the JNK pathway that was not inhibited by the pharmacological mixed lineage kinase (MLK) inhibitor CEP1347. NRAGE induced cytosolic accumulation of cytochrome c, activation of Caspases-3, -9 and -7, and caspase-dependent cell death. Blocking JNK and c-Jun action by overexpression of the JNK-binding domain of JIP1 or dominant-negative c-Jun ablated NRAGE-mediated caspase activation and NRAGE-induced cell death. These findings identify NRAGE as a p75NTR interactor capable of inducing caspase activation and cell death through a JNK-dependent mitochondrial apoptotic pathway.